Comparing the Effectiveness of Multimodal vs Monomodal Digital Flashcards for L2 Vocabulary Learning - Hicks, Joshua; Marnita, Rina; Oktavianus, Oktavianus (Studies in English Language and Education, 2025)
This applied psycholinguistics study explores whether multimodal flashcards (containing text, audio, and a picture) are more effective than monomodal flashcards (containing text only) as a tool for learning the meanings of novel second-language (L2) concrete nouns. A flashcard application that utilizes active recall testing and spaced repetition Anki was used as a research instrument. A within-subject design was used: Each participant (n = 25) studied a total of 30 L2-L1 (EsperantoIndonesian) word pairs over the course of 7 study sessions using an assortment of 15 multimodal and 15 monomodal flashcards, with each word pair being presented multimodally to approximately half of participants and monomodally to the other half. When (re)viewing the answer side of a card, participants were instructed to tap Good if they recalled the answer correctly or Again if not. Recall accuracy data for the two card types was collected and then analysed using a paired t-test, the results of which indicated that the number of user-initiated reviews (Again count, which is indicative of the number of memory lapses) was significantly higher for monomodal flashcards (M = 83.2 ,SD = 61.3) than for multimodal flashcards (M = 58.8 ,SD = 32.1), t(24) = 3.4, p = .001. These results support the hypothesis that multimodal flashcards are more effective than monomodal flashcards as a tool for learning the meanings of L2 concrete nouns. By implication, language learners can enhance their recall accuracy of L2 concrete nouns by creating and using flashcards that include multiple semantically congruent modes.